Deep Dark Futures: Foresighting Human Impacts on Mesopelagic Ecosystem Services - Ben Scoulding; Alistair J. Hobday; Rowan Trebilco; Heidi Pethybridge; Ingrid van Putten; Katherine Baker; Karen Evans; David Green; Eriko Hoshino; Haris Kunnath; Clothilde Langlais; Tim P. Lynch; et al. (Fish and Fisheries, 2026)
Most of the global mesopelagic zone lies beyond the jurisdiction of any single government or entity, making equitable access and sustainable management for ecosystem services (ES) difficult. Here, a foresighting approach was used to examine the plausible consequences of four speculative scenarios of human activity on the mesopelagic zone and its associated ES. Large‐scale Harvest represented the provisioning ES, with concerns over unsustainable removal of mesopelagic biota. Climate Mitigation, a regulating ES, involved harvesting and then dumping mesopelagic biota to maximise carbon drawdown. In Geopolitical Manoeuvring, the scenario focused on cultural ES; mesopelagic fisheries were used as a geopolitical instrument to assert claims over ocean spaces. Finally, Mineral Extraction, a supporting ES, considered the impact of deep‐sea mining on mesopelagic ecosystems. Drivers and indicators for each scenario were identified, and qualitative network models were created to assess impact on the different system components using press perturbations. Model outputs highlighted the central role that mesopelagic biota play in supporting and regulating other ecosystem components and the likely negative impacts of reduced biomass on higher order predators and ocean carbon storage. Interestingly, biological indicators performed poorly as early warning signals of change across all scenarios; instead, the most effective indicators were related to science and technology, economics and governance. International agreements for sustainable use of the mesopelagic zone are needed to avoid loss of ES underpinning all scenarios. While this foresighting focused on the mesopelagic zone, the approach of developing scenarios, models and indicators has broader applicability to studies of other systems.

AI-driven knowledge synthesis for food web parameterisation - Scott Spillias; Elizabeth A. Fulton; Fabio Boschetti; Cathy Bulman; Joanna Strzelecki; Rowan Trebilco (Environmental Modelling & Software, 2026)

‘State of the Environment’ reports require integrated and holistic approaches – Lessons from Australia’s marine experience - Rowan Trebilco; Cass Hunter; Mibu Fischer; Karen Evans; Alistair J. Hobday; Linda Thomas (Marine Policy, 2025)

Fish and invertebrate communities show greater day–night partitioning on tropical than temperate reefs - Tyson R. Jones; Graham J. Edgar; Rowan Trebilco; Camille Mellin; Rick D. Stuart‐Smith; Lara Denis‐Roy; Olivia J. Johnson; Matthew Rose; Scott D. Ling (Ecology, 2025)
Diel partitioning of animals within ecological communities is widely acknowledged, yet rarely quantified. Investigation of most ecological patterns and processes involves convenient daylight sampling, with little consideration of the contributions of nocturnal taxa, particularly in marine environments. Here we assess diel partitioning of reef faunal assemblages at a continental scale utilizing paired day and night visual census across 54 shallow tropical and temperate reefs around Australia. Day–night differences were most pronounced in the tropics, with fishes and invertebrates displaying distinct and opposing diel occupancy on coral reefs. Tropical reefs in daytime were occupied primarily by fishes not observed at night (64% of all species sighted across day and night, and 71% of all individuals). By night, substantial emergence of invertebrates not otherwise detected during sunlit hours occurred (56% of all species, and 45% of individuals). Nocturnal emergence of tropical invertebrates corresponded with significant declines in the richness and biomass of predatory and herbivorous diurnal fishes. In contrast, relatively small diel changes in fishes active on temperate reefs corresponded to limited nocturnal emergence of temperate invertebrates. This reduced partitioning may, at least in part, be a result of strong top‐down pressures from fishes on invertebrate communities, either by predation or competitive interference. For shallow reefs, the diel cycle triggers distinct emergence and retreat of faunal assemblages and associated trophic patterns and processes, which otherwise go unnoticed during hours of regular scientific monitoring. Improved understanding of reef ecology, and management of reef ecosystems, requires greater consideration of nocturnal interactions. Without explicit sampling of nocturnal patterns and processes, we may be missing up to half of the story when assessing ecological interactions.

Co-designing a multi-criteria approach to ranking hazards to and from Australia’s emerging offshore blue economy - Mischa P. Turschwell; Christopher J. Brown; Myriam Lacharité; Jess Melbourne-Thomas; Keith R. Hayes; Rodrigo H. Bustamante; Jeffrey M. Dambacher; Karen Evans; Pedro Fidelman; Darla Hatton MacDonald; Ingrid Van Putten; Graham Wood; et al. (Environmental Science & Policy, 2023)

KRILLPODYM: a mechanistic, spatially resolved model of Antarctic krill distribution and abundance - David B. Green; Olivier Titaud; Sophie Bestley; Stuart P. Corney; Mark A. Hindell; Rowan Trebilco; Anna Conchon; Patrick Lehodey (Frontiers in Marine Science, 2023)
Robust prediction of population responses to changing environments requires the integration of factors controlling population dynamics with processes affecting distribution. This is true everywhere but especially in polar pelagic environments. Biological cycles for many polar species are synchronised to extreme seasonality, while their distributions may be influenced by both the prevailing oceanic circulation and sea-ice distribution. Antarctic krill (krill, Euphausia superba ) is one such species exhibiting a complex life history that is finely tuned to the extreme seasonality of the Southern Ocean. Dependencies on the timing of optimal seasonal conditions have led to concerns over the effects of future climate on krill’s population status, particularly given the species’ important role within Southern Ocean ecosystems. Under a changing climate, established correlations between environment and species may breakdown. Developing the capacity for predicting krill responses to climate change therefore requires methods that can explicitly consider the interplay between life history, biological conditions, and transport. The Spatial Ecosystem And Population Dynamics Model (SEAPODYM) is one such framework that integrates population and general circulation modelling to simulate the spatial dynamics of key organisms. Here, we describe a modification to SEAPODYM, creating a novel model – KRILLPODYM – that generates spatially resolved estimates of krill biomass and demographics. This new model consists of three major components: (1) an age-structured population consisting of five key life stages, each with multiple age classes, which undergo age-dependent growth and mortality, (2) six key habitats that mediate the production of larvae and life stage survival, and (3) spatial dynamics driven by both the underlying circulation of ocean currents and advection of sea-ice. We present the first results of KRILLPODYM, using published deterministic functions of population processes and habitat suitability rules. Initialising from a non-informative uniform density across the Southern Ocean our model independently develops a circumpolar population distribution of krill that approximates observations. The model framework lends itself to applied experiments aimed at resolving key population parameters, life-stage specific habitat requirements, and dominant transport regimes, ultimately informing sustainable fishery management.

Species distribution models describe spatial variability in mesopelagic fish abundance in the Southern Ocean - Briannyn L. Woods; Anton P. Van de Putte; Mark A. Hindell; Ben Raymond; Ryan A. Saunders; Andrea Walters; Rowan Trebilco (Frontiers in Marine Science, 2023)
Introduction Mesopelagic fishes play a central role in the transfer of energy through open-ocean food webs, particularly in the Southern Ocean where they are both important predators of zooplankton and a key prey group for many higher predators. However, they are notoriously difficult to sample, which has limited our understanding of the bio-physical predictors of their abundance and spatiotemporal variability. Species distribution models can be used to help understand species’ ecological requirements by relating records of their presence or abundance to environmental data. Methods Here, we used data from Myctobase – a new circumpolar database of mesopelagic fishes – to model patterns in abundance of eight key myctophid species (family Myctophidae) and the genus Bathylagus in the Southern Ocean south of 45°S. We developed species-specific boosted regression tree models to obtain circumpolar predictions of abundance. Average daytime and night-time summer predictions for the period 1997 to 2011 at 0 to 200m depths were generated for each species. Results Depth and solar position were important predictors and species were stratified in their depth distribution. For all species, except for G. nicholsi , there was an interaction between depth of capture and solar position, reflecting diel vertical migration. Other important variables included sea surface temperature, dissolved oxygen at 200 m, chlorophyll a , and sea surface height, indicating an association with water mass properties. Circumpolar patterns of abundance varied between species with some displaying affinities for oceanic regions at Antarctic latitudes (e.g., E. antarctica and Bathylagus spp.) or sub-Antarctic latitudes (e.g., K. anderssoni and P. tenisoni ); and affinities for shelf regions (e.g., P. bolini and G. nicholsi ). Discussion Our findings suggest that the abundance of mesopelagic fish is influenced by diel vertical migration and meso- and sub-mesoscale oceanographic features, with the Polar Front being a major delimiting feature. Our study showed contrasting patterns in community composition with higher species diversity north of the Polar Front that might be indicative of latitudinal variability in food web structure. Our spatial analysis is an important step toward resolving what determines important habitat for mesopelagic fishes, providing foundational information for understanding shifting food web dynamics into the future.

Safeguarding marine life: conservation of biodiversity and ecosystems - Delphi Ward; Jessica Melbourne-Thomas; Gretta T. Pecl; Karen Evans; Madeline Green; Phillipa C. McCormack; Camilla Novaglio; Rowan Trebilco; Narissa Bax; Madeleine J. Brasier; Emma L. Cavan; Graham Edgar; et al. (Reviews in Fish Biology and Fisheries, 2022)
Marine ecosystems and their associated biodiversity sustain life on Earth and hold intrinsic value. Critical marine ecosystem services include maintenance of global oxygen and carbon cycles, production of food and energy, and sustenance of human wellbeing. However marine ecosystems are swiftly being degraded due to the unsustainable use of marine environments and a rapidly changing climate. The fundamental challenge for the future is therefore to safeguard marine ecosystem biodiversity, function, and adaptive capacity whilst continuing to provide vital resources for the global population. Here, we use foresighting/hindcasting to consider two plausible futures towards 2030: a business-as-usual trajectory (i.e. continuation of current trends), and a more sustainable but technically achievable future in line with the UN Sustainable Development Goals. We identify key drivers that differentiate these alternative futures and use these to develop an action pathway towards the desirable, more sustainable future. Key to achieving the more sustainable future will be establishing integrative (i.e. across jurisdictions and sectors), adaptive management that supports equitable and sustainable stewardship of marine environments. Conserving marine ecosystems will require recalibrating our social, financial, and industrial relationships with the marine environment. While a sustainable future requires long-term planning and commitment beyond 2030, immediate action is needed to avoid tipping points and avert trajectories of ecosystem decline. By acting now to optimise management and protection of marine ecosystems, building upon existing technologies, and conserving the remaining biodiversity, we can create the best opportunity for a sustainable future in 2030 and beyond.

Warming world, changing ocean: mitigation and adaptation to support resilient marine systems - Rowan Trebilco; Aysha Fleming; Alistair J. Hobday; Jess Melbourne-Thomas; Amelie Meyer; Jan McDonald; Phillipa C. McCormack; Kelli Anderson; Narissa Bax; Stuart P. Corney; Leo X. C. Dutra; Hannah E. Fogarty; et al. (Reviews in Fish Biology and Fisheries, 2022)

Poleward bound: adapting to climate-driven species redistribution - Jess Melbourne-Thomas; Asta Audzijonyte; Madeleine J. Brasier; Katherine A. Cresswell; Hannah E. Fogarty; Marcus Haward; Alistair J. Hobday; Heather L. Hunt; Scott D. Ling; Phillipa C. McCormack; Tero Mustonen; Kaisu Mustonen; et al. (Reviews in Fish Biology and Fisheries, 2022)

Corrigendum: Future Risk for Southern Ocean Ecosystem Services Under Climate Change - Rachel D. Cavanagh; Jess Melbourne-Thomas; Susie M. Grant; David K. A. Barnes; Kevin A. Hughes; Svenja Halfter; Michael P. Meredith; Eugene J. Murphy; Rowan Trebilco; Simeon L. Hill (Frontiers in Marine Science, 2021)

Stakeholder Engagement in Decision Making and Pathways of Influence for Southern Ocean Ecosystem Services - Josh Solomonsz; Jess Melbourne-Thomas; Andrew Constable; Rowan Trebilco; Ingrid van Putten; Lyn Goldsworthy (Frontiers in Marine Science, 2021)
Southern Ocean ecosystem management is characterized by a unique and complex international network of stakeholders and stakeholder relationships (a ‘transactional landscape’) relating to the globally significant services that these ecosystems support. This transactional landscape spans governments, industry (fishing and tourism), scientific research, conservation non-government organizations, civil society, and international decision-making forums. We used a network approach for stakeholder mapping to provide the first description of the transactional landscape for Southern Ocean ecosystem management – both in terms of the connections between stakeholders and ecosystem services, and directly between stakeholder groups. We considered 65 stakeholders and their relationships to 12 provisioning, regulating, supporting and cultural ecosystem services. An analysis of the connections within this network reveals differences in the degree of connectivity between stakeholders and ecosystem services. Notably, ecosystem science facilitates high connectivity between stakeholders and provisioning services, but there is little connectivity between stakeholders and supporting services. We then applied a formal ‘values-rules-knowledge’ framework to a set of case studies to analyze the decision-making process in relation to Southern Ocean ecosystem services, as well as the relative importance of different stakeholder groups which were considered in the network analysis. Our analyses suggest that emphases for decision making have been on knowledge and rules, but that wider consideration of values across the broader stakeholder landscape – together with science (knowledge) and governance (rules) – might better support decision making for Southern Ocean ecosystem conservation and management, and provide a stronger foundation for sustainable provision of ecosystem services into the future.

Combating ecosystem collapse from the tropics to the Antarctic - Dana M. Bergstrom; Barbara C. Wienecke; John van den Hoff; Lesley Hughes; David B. Lindenmayer; Tracy D. Ainsworth; Christopher M. Baker; Lucie Bland; David M. J. S. Bowman; Shaun T. Brooks; Josep G. Canadell; Andrew J. Constable; et al. (Global Change Biology, 2021)
Globally, collapse of ecosystems—potentially irreversible change to ecosystem structure, composition and function—imperils biodiversity, human health and well‐being. We examine the current state and recent trajectories of 19 ecosystems, spanning 58° of latitude across 7.7 M km 2 , from Australia's coral reefs to terrestrial Antarctica. Pressures from global climate change and regional human impacts, occurring as chronic ‘presses’ and/or acute ‘pulses’, drive ecosystem collapse. Ecosystem responses to 5–17 pressures were categorised as four collapse profiles—abrupt, smooth, stepped and fluctuating. The manifestation of widespread ecosystem collapse is a stark warning of the necessity to take action. We present a three‐step assessment and management framework (3As Pathway Awareness , Anticipation and Action ) to aid strategic and effective mitigation to alleviate further degradation to help secure our future.

The use of swimmers from sediment traps to measure summer community structure of Southern Ocean pteropods - Christine K. Weldrick; Ryosuke Makabe; Kohei Mizobata; Masato Moteki; Tsuneo Odate; Shintaro Takao; Rowan Trebilco; Kerrie M. Swadling (Polar Biology, 2021)

Globally consistent reef size spectra integrating fishes and invertebrates - Freddie J. Heather; Julia L. Blanchard; Graham J. Edgar; Rowan Trebilco; Rick D. Stuart‐Smith (Ecology Letters, 2021)
The frequency distribution of individual body sizes in animal communities (i.e. the size spectrum) provides powerful insights for understanding the energy flux through food webs. However, studies of size spectra in rocky and coral reef communities typically focus only on fishes or invertebrates due to taxonomic and data constraints, and consequently ignore energy pathways involving the full range of macroscopic consumer taxa. We analyse size spectra with co‐located fish and mobile macroinvertebrate data from 3369 reef sites worldwide, specifically focusing on how the addition of invertebrate data alters patterns. The inclusion of invertebrates steepens the size spectrum, more so in temperate regions, resulting in a consistent size spectrum slope across latitudes, and bringing slopes closer to theoretical expectations based on energy flow through the system. These results highlight the importance of understanding contributions of both invertebrates and fishes to reef food webs worldwide.

Future Risk for Southern Ocean Ecosystem Services Under Climate Change - Rachel D. Cavanagh; Jess Melbourne-Thomas; Susie M. Grant; David K. A. Barnes; Kevin A. Hughes; Svenja Halfter; Michael P. Meredith; Eugene J. Murphy; Rowan Trebilco; Simeon L. Hill (Frontiers in Marine Science, 2021)
The Southern Ocean supports ecosystem services that are important on a global scale. Climate change and human activities (tourism, fishing, and research) will affect both the demand for, and the provision of, these services into the future. Here we synthesize recent assessments of the current status and expected future climate-driven changes in Southern Ocean ecosystems and evaluate the potential consequences of these changes for the provision of ecosystem services. We explore in detail three key services (the ‘blue carbon’ pathway, the Antarctic krill fishery, and Antarctic tourism), tracing the consequences of climate change from physical drivers through biological impacts to the benefits to humans. We consider potential non-climatic drivers of change, current and future demands for the services, and the main global and regional policy frameworks that could be used to manage risks to the provision of these services in a changing climate. We also develop a formal representation of the network of interactions between the suite of potential drivers and the suite of services, providing a framework to capture the complexity of this network and its embedded feedback loops. Increased consideration of the linkages and feedbacks between drivers and ecosystem services will be required to underpin robust management responses into the future.

Delivering Sustained, Coordinated, and Integrated Observations of the Southern Ocean for Global Impact - Louise Newman; Petra Heil; Rowan Trebilco; Katsuro Katsumata; Andrew Constable; Esmee van Wijk; Karen Assmann; Joana Beja; Phillippa Bricher; Richard Coleman; Daniel Costa; Steve Diggs; et al. (Frontiers in Marine Science, 2019)

Using stable isotope data to advance marine food web modelling - Stacey A. McCormack; Rowan Trebilco; Jessica Melbourne-Thomas; Julia L. Blanchard; Elizabeth A. Fulton; Andrew Constable (Reviews in Fish Biology and Fisheries, 2019)

Productivity and fishing pressure drive variability in fish parasite assemblages of the Line Islands, equatorial Pacific - Chelsea L. Wood; Julia K. Baum; Sheila M. W. Reddy; Rowan Trebilco; Stuart A. Sandin; Brian J. Zgliczynski; Amy A. Briggs; Fiorenza Micheli (Ecology, 2015)
Variability in primary productivity and fishing pressure can shape the abundance, species composition, and diversity of marine life. Though parasites comprise nearly half of marine species, their responses to these important forces remain little explored. We quantified parasite assemblages at two spatial scales, across a gradient in productivity and fishing pressure that spans six coral islands of the Line Islands archipelago and within the largest Line Island, Kiritimati, which experiences a west‐to‐east gradient in fishing pressure and upwelling‐driven productivity. In the across‐islands data set, we found that increasing productivity was correlated with increased parasite abundance overall, but that the effects of productivity differed among parasite groups. Trophically transmitted parasites increased in abundance with increasing productivity, but directly transmitted parasites did not exhibit significant changes. This probably arises because productivity has stronger effects on the abundance of the planktonic crustaceans and herbivorous snails that serve as the intermediate hosts of trophically transmitted parasites than on the higher‐trophic level fishes that are the sole hosts of directly transmitted parasites. We also found that specialist parasites increased in response to increasing productivity, while generalists did not, possibly because specialist parasites tend to be more strongly limited by host availability than are generalist parasites. After the effect of productivity was controlled for, fishing was correlated with decreases in the abundance of trophically transmitted parasites, while directly transmitted parasites appeared to track host density; we observed increases in the abundance of parasites using hosts that experienced fishing‐driven compensatory increases in abundance. The within‐island data set confirmed these patterns for the combined effects of productivity and fishing on parasite abundance, suggesting that our conclusions are robust across a span of spatial scales. Overall, these results indicate that there are strong and variable effects of anthropogenic and natural drivers on parasite abundance and taxonomic richness. These effects are likely to be mediated by parasite traits, particularly by parasite transmission strategies.

Unintended Cultivation, Shifting Baselines, and Conflict between Objectives for Fisheries and Conservation - CHRISTOPHER J. BROWN; ROWAN TREBILCO (Conservation Biology, 2014)
The effects of fisheries on marine ecosystems, and their capacity to drive shifts in ecosystem states, have been widely documented. Less well appreciated is that some commercially valuable species respond positively to fishing‐induced ecosystem change and can become important fisheries resources in modified ecosystems. Thus, the ecological effects of one fishery can unintentionally increase the abundance and productivity of other fished species (i.e., cultivate). We reviewed examples of this effect in the peer‐reviewed literature. We found 2 underlying ecosystem drivers of the effect: trophic release of prey species when predators are overfished and habitat change. Key ecological, social, and economic conditions required for one fishery to unintentionally cultivate another include strong top–down control of prey by predators, the value of the new fishery, and the capacity of fishers to adapt to a new fishery. These unintended cultivation effects imply strong trade‐offs between short‐term fishery success and conservation efforts to restore ecosystems toward baseline conditions because goals for fisheries and conservation may be incompatible. Conflicts are likely to be exacerbated if fisheries baselines shift relative to conservation baselines and there is investment in the new fishery. However, in the long‐term, restoration toward ecosystem baselines may often benefit both fishery and conservation goals. Unintended cultivation can be identified and predicted using a combination of time‐series data, dietary studies, models of food webs, and socioeconomic data. Identifying unintended cultivation is necessary for management to set compatible goals for fisheries and conservation. Cultivo Accidental, Líneas de Base Cambiantes y el Conflicto entre los Objetivos para las Pesquerías y la Conservación